2011
DOI: 10.1200/jop.2011.000302
|View full text |Cite
|
Sign up to set email alerts
|

Impact of New Drugs and Biologics on Colorectal Cancer Treatment and Costs

Abstract: Purpose: To compare medical expenditures of patients receiving old and new colorectal cancer (CRC) regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…12 Until recently, 3 regimens dominated firstline treatment of CRC: FU, available since the 1960s, which has been routinely administered with FU/LV since the early 1990s or with irinotecan (IFL or Folfiri) since 2000. 8,13,14 In the past decade, the U.S. Food and Drug Administration approved several new drugs, such as capecitabine, oxaliplatin, bevacuzimab, cetuximab, and panitumumab, which have been widely used in the treatment of CRC patients. 8 This study found that biologics, including bevacuzimab, cetuximab, and panitumumab, were more likely added into regimens in the third + lines as compared with earlier lines.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Until recently, 3 regimens dominated firstline treatment of CRC: FU, available since the 1960s, which has been routinely administered with FU/LV since the early 1990s or with irinotecan (IFL or Folfiri) since 2000. 8,13,14 In the past decade, the U.S. Food and Drug Administration approved several new drugs, such as capecitabine, oxaliplatin, bevacuzimab, cetuximab, and panitumumab, which have been widely used in the treatment of CRC patients. 8 This study found that biologics, including bevacuzimab, cetuximab, and panitumumab, were more likely added into regimens in the third + lines as compared with earlier lines.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…8,13,14 In the past decade, the U.S. Food and Drug Administration approved several new drugs, such as capecitabine, oxaliplatin, bevacuzimab, cetuximab, and panitumumab, which have been widely used in the treatment of CRC patients. 8 This study found that biologics, including bevacuzimab, cetuximab, and panitumumab, were more likely added into regimens in the third + lines as compared with earlier lines.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new biologic operators-bevacizumab, cetuximab, and panitumumabare regularly alluded to as monoclonal antibodies. In fact; these antibodies encourage immune responses against quickly multiplying cancer cells [19]. Drug repurposing has several advantages and the endeavors have been driven by a few imperative components including; the access to expanding measures of experimental information, better comprehension of compound poly pharmacology and biological information mining.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, the costs of health care are not increasing only in pharmaceuticals but in many areas, including hospitalizations and imaging. 30,31 In addition, many pharmaceutical companies have been generous in providing medications at low or no cost to qualifying patients. The cost of care is a systemwide problem that includes many participants, including health care professionals, device manufacturers, and medical supply manufacturers.…”
Section: Why Are Cancer Drugs So Expensive?mentioning
confidence: 99%